Methodology of determination of the optimal investment strategy in single-fuel CHP plants. (November 2020) - Bartnik, Ryszard; Hnydiuk-Stefan, Anna; Buryn, Zbigniew; Skomudek, Waldemar; Otawa, Aleksandra
Abstract: This paper presents comprehensive diagrams applied in the search for the optimal strategy for investing in heat sources and analysis of the impact of technical and economic parameters on specific heat production costs in single-fuel combined heat and power plants. An innovative methodology was applied to find for the specific cost of heat production in various technologies. The results regarding the specific cost of heat production in combined power heat and sources systems are discussed in this paper. The graphs are universal and can be used with regard to various combinations of technical and economic parameters playing a decisive role in the cost of heat production. In addition, the results of the calculations are presented in the function of the value of the annual cogeneration factor, the value of which is dependent on the technology applied in combined heat and power production. Using the presented innovative methodology and graphs developed on its basis, it is possible to select the most favorable heat production technology, for which the specific cost of heat production is the lowest, for any cost of fuel, price of electric energy and cost of the purchase of CO2 emission permits.